2014
DOI: 10.1093/jnci/dju153
|View full text |Cite
|
Sign up to set email alerts
|

Reassurance Against Future Risk of Precancer and Cancer Conferred by a Negative Human Papillomavirus Test

Abstract: Primary human papillomavirus (HPV) testing (without concurrent Pap tests) every 3 years is under consideration in the United States as an alternative to the two recommended cervical cancer screening strategies: primary Pap testing every 3 years, or concurrent Pap and HPV testing ("cotesting") every 5 years. Using logistic regression and Weibull survival models, we estimated and compared risks of cancer and cervical intraepithelial neoplasia grade 3 or worse (CIN3+) for the three strategies among 1011092 women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
198
1
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(214 citation statements)
references
References 14 publications
9
198
1
6
Order By: Relevance
“…A very large trial was performed at Kaiser Permanente Northern California (KPNC) in a routine clinical practice in which cotesting with cytology and HPV at 3-year intervals was the standard of care (181). The trial included more than 1 million women who were HPV negative and had normal cytology at entry.…”
Section: High-risk Hpv Detection As a First-line Test In Primary Cervmentioning
confidence: 99%
See 1 more Smart Citation
“…A very large trial was performed at Kaiser Permanente Northern California (KPNC) in a routine clinical practice in which cotesting with cytology and HPV at 3-year intervals was the standard of care (181). The trial included more than 1 million women who were HPV negative and had normal cytology at entry.…”
Section: High-risk Hpv Detection As a First-line Test In Primary Cervmentioning
confidence: 99%
“…The trial included more than 1 million women who were HPV negative and had normal cytology at entry. The most recent analysis was focused on providing further information on the utility of HPV primary screening by specifically looking at future cancer risks after negative screening results (181). The analysis found that a negative HPV test alone provides a very high 3-year assurance against CIN 3 or cancer that is either better than or similar to that with the current guideline intervals of 3 years for cytology and 5 years for cytology plus HPV cotest.…”
Section: High-risk Hpv Detection As a First-line Test In Primary Cervmentioning
confidence: 99%
“…Snijders et al 2013, and other studies mentioned above). In 523 addition, a negative HPV test is more predictive for a reduced three-year risk of 524 developing cervical cancer than a negative Pap smear (Gage et al 2014). Therefore, 525 screening for hrHPV through self-sampling with appropriate follow-up for positive results 526 may potentially be more effective than routine Pap smears (Schmeink et al 2011).…”
Section: Discussion and Conclusion 504mentioning
confidence: 99%
“…Testing for the presence of hrHPV has 102 proven to be more sensitive for cervical cancer precursors than the Pap test (Mayrand 103 et al 2007). In a large Kaiser Permanente study involving over 1 million women, three-104 year risks for CIN3 or worse (CIN3+) or cancer following an HPV-negative result were 105 lower than those following a Pap-negative result, suggesting that testing for HPV is 106 more predictive for the reduced three-year risk of developing cervical cancer and thus a 107 better strategy for cervical cancer screening than a Pap smear (Gage et al 2014). 108…”
Section: Hc2 Hpv Assay and Several Pcr Amplification-based Tests Sucmentioning
confidence: 99%
“…Testing for high-risk HPV genotypes (hrHPV) has recently been shown to be a better indicator of cervical cancer risk than the cytology test (3)(4)(5). Several countries have changed their cervical cancer screening guidelines, accordingly.…”
Section: Introductionmentioning
confidence: 99%